2016
DOI: 10.14348/molcells.2016.0050
|View full text |Cite
|
Sign up to set email alerts
|

MiR-144-3p and Its Target Gene β-Amyloid Precursor Protein Regulate 1-Methyl-4-Phenyl-1,2-3,6-Tetrahydropyridine-Induced Mitochondrial Dysfunction

Abstract: MicroRNAs (miRNAs) have been reported to be involved in many neurodegenerative diseases. The present study focused on the role of hsa-miR-144-3p in one of the neurodegenerative diseases, Parkinson’s disease (PD). Our study showed a remarkable down-regulation of miR-144-3p expression in 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-treated SH-SY5Y cells. MiR-144-3p was then overexpressed and silenced in human SH-SY5Y cells by miRNA-mimics and miRNA-inhibitor transfections, respectively. Furthermore, β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 32 publications
(39 reference statements)
1
19
0
1
Order By: Relevance
“…In the same cells, miR-144-3p overexpression significantly inhibited the protein expression of b-amyloid precursor protein (APP). In the same study, noticeable increase in cellular ATP, cell viability, and the relative copy number of mitochondrial DNA was noted, suggesting that miR-144-3p plays an important role in maintaining mitochondrial function, along with its target gene APP (Li et al, 2016).…”
Section: Relationship Of Mirnas In Mitochondrial Diseases and Dysfuncmentioning
confidence: 73%
See 2 more Smart Citations
“…In the same cells, miR-144-3p overexpression significantly inhibited the protein expression of b-amyloid precursor protein (APP). In the same study, noticeable increase in cellular ATP, cell viability, and the relative copy number of mitochondrial DNA was noted, suggesting that miR-144-3p plays an important role in maintaining mitochondrial function, along with its target gene APP (Li et al, 2016).…”
Section: Relationship Of Mirnas In Mitochondrial Diseases and Dysfuncmentioning
confidence: 73%
“…Furthermore, miR-34a inhibits the PPAR a signaling pathway by binding to sites in the 3¢ UTR of adipoR2 genes and also involved in the 5¢-adenosine monophosphateactivated protein kinase pathway in mitochondria (Wen et al, 2018). Li et al (2016) in their study showed a remarkable upregulation of miR-144-3p with increased expression of key genes involved in maintaining the mitochondrial function, including peroxisome proliferator-activated receptor g coactivator-1a (PGC-1a), nuclear respiratory factor 1, and mitochondrial transcription factor A. In the same cells, miR-144-3p overexpression significantly inhibited the protein expression of b-amyloid precursor protein (APP).…”
Section: Relationship Of Mirnas In Mitochondrial Diseases and Dysfuncmentioning
confidence: 95%
See 1 more Smart Citation
“…To this end, we determined the expression of the proteins associated with energy metabolism and autophagy functional status. Since mitochondrial biogenesis is regulated by the proliferator-activated receptor-␥ coactivator-1-␣ (PGC-1␣)-nuclear factor-E2-related factor 2 (Nrf2)mitochondrial transcription factor A (TFAM) signal pathway, the decreased expression of PGC-1␣, NRF-1, and TFAM was observed in AD (19,30). In the present study, we first measured the protein expression level of PGC-1␣ in hippocampal tissue.…”
Section: Resultsmentioning
confidence: 99%
“…3, для которых в ANDSystem не было информации об их ассоциациях с БП. Гены TP53, JUN, BCL2 и APP достаточно активно обсуждаются в литературе в связи с БП (Rekha, Selvakumar, 2014;Li et al, 2016;Oh et al, 2016;Lu et al, 2017). Ген TP53 кодирует белок-опухолевый супрессор, который регулирует многие процессы, в том числе клеточный цикл, апоптоз, старение клетки, репарацию ДНК и метаболизм.…”
Section: результаты и обсуждениеunclassified